Effect of calmodulin on the stimulation of capacitation and acrosome reaction of frozen thawed bull spermatozoa - Akter, QS; Tareq, KMA; Hamano, K; Gilchrist, RB (Bangladesh Journal of Animal Science, 2017)
Capacitation and acrosome reaction (AR) are the prerequisites for successful fertilization by mammalian spermatozoa. Intracellular calcium (Ca2+) has a regulatory role in sperm motility, capacitation, and AR. Calmodulin (CaM) antagonists calmidazolium (CZ) and N-(6-aminohexyl)-5-chloro-1-naphthalenesulfonamide (W7) were used to investigate the possible role of CaM, a Ca2+ specific binding protein, on motility, capacitation and AR of frozen-thawed bovine spermatozoa. Capacitation and AR in sperm were evaluated by using chlortetracycline (CTC) staining technique. Addition of the 1 mM dibutyryl cAMP (dbcAMP) and 100 ?M 1-methy l-3-isobutylxanthine (IBMX) to CaM antagonists treated sperm incubated in the presence of NaHCO3 and CaCl2 in media overcome the inhibitory effects of these antagonists to support capacitation and AR at 4 h of incubation period. In contrast, addition of dbcAMP with IBMX induced AR in spermatozoa incubated with NaHCO3-free medium but these compounds did not induce AR in cells incubated in CaCl2-free medium. However, the addition of dbcAMP and IBMX partially, but significantly (p<0.01) reversed the inhibitory effect of W7 and CZ on the sperm capacitation and AR. These results suggest that CaM may play an important role in the regulation of capacitation and AR in frozen-thawed bovine spermatozoa. Bang. J. Anim. Sci. 2016. 45 (3): 1-9